Winter wheat resistance to main stress factors of environment and weather (review - O. A. Dubinina (Зерновое хозяйство России, 2018)
Winter wheat resistance to main stress factors of environment and weather (review) Difficult weather-climatic conditions put a number of important tasks before winter wheat breeding. Some years are characterized with unfavourable stress factors of environment which should be taken into account during winter wheat breeding. Among all year with good growing conditions for winter crops there are some years with sudden change of temperature in winter months and in spring, when plants suffer from freezing, bulging, waterlogging that result in thinning of crops and even crop failure. Early spring and later spring frosts reduce crop productivity. Eastern hot dry winds together with high temperatures at the end of June-beginning of July negatively affect on grain filling and ripeness. Pouring precipitations in May-June can cause hard lodging of crops and can become favourable for the development of diseases. All these weather factors make winter wheat breeding more difficult. The article presents and summarizes the study results of winter wheat tolerance to the main stress factors of environment and weather obtained by various researchers.